REORIENTASI PEMBELAJARAN FIKIH DI MADRASAH - Rakhmawati Rakhmawati; Muh. Rusli; Firmansah Kobandaha (LP2M IAIN Sultan Amai Gorontalo, 2024)
abstract The learning of fiqh in madrasah generally emphasizes religious comprehension without linking it to contemporary socio-religious problems. There is also the problem of the traditional curriculum that tends to be defended by traditionalists and conservative scholars. This article aims to reorient fiqh learning by answering various problems that surround it. In answering these problems, the method used is qualitative with a content analysis approach. The results show that maximum effort is needed to review the curriculum, the need for integration of critical thinking and problem-solving skills in the fiqh curriculum; Application of various methods that suit the needs of students; Fulfillment of the number of educators who are equipped with various training in order to support their professionalism; Commitment to contemporary fiqh issues and ethical dilemmas; And Collaboration with educational institutions and Islamic jurists.